Peran Pemerintah Kota Cilegon Dalam Pelaksanaan Sistem Merit Untuk Mewujudkan ASN Yang Profesional Di Pemerintah Kota Cilegon Berdasarkan Undang-Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara - Khofifah, Bunga Nur (Beleid, 2023)
The implementation of the merit system in Cilegon City Government is to find out whether the 8 (eight) important aspects used in the merit system assessment are properly implemented and are able to produce professional apparatus or not. The method used in this study is a review of 8 (eight) important aspects of the merit system assessment based on the mandate of law number 5 of 2014 concerning State Civil Apparatuses also based on KASN assessments through Regulation of the State Civil Apparatus Commission Number 9 of 2019 concerning Procedures for Assessment Mandiri Merit System in the Management of State Civil Apparatuses in Government Agencies that apply to the problems discussed in this study. Research that uses a statutory approach is often referred to as normative legal research. The results of this research are that the City Government of Cilegon has not fully implemented the 8 important aspects of the merit system assessment as mandated by Article 51 of Law Number 5 of 2014 concerning State Civil Apparatuses that ASN management is organized based on a merit system.